Applications of nonverbal communication - Riggio, Ronald E.; Feldman, Robert S. (Robert Stephen), 1947- (Claremont Symposium on Applied Social Psychology Series., 2005)
The goal of this edited volume is to present the practical applications suggested by research in non-verbal communication, as well as to highlight the limitations-noting where we simply do not yet know enough to safely and fully inform practice.